2021
DOI: 10.1186/s13643-021-01619-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-based educational interventions for prevention of type II diabetes: a global systematic review and meta-analysis

Abstract: Purpose Our objective was to estimate the change in community-based education interventions throughout the world that may effectuate in risk parameters of type II diabetes (T2D), including the diabetes incidence rate, fasting blood glucose, hemoglobin A1C, body mass index, waist circumference, and systolic and diastolic blood pressure. Methods A comprehensive search for globally eligible studies was conducted on PubMed, Embase, ProQuest, CINAHL nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
2
0
2
Order By: Relevance
“…The findings are in line with those of the previous review that showed the positive effects of group-based self-management education interventions on HbA1c, FBG, body weight, WC, TG and diabetes knowledge [98]. Another review, however, showed that there was no effect of community-based educational interventions on SBP and DBP [99]. Overall, these findings support the potential clinical, behavioural and psychological efficacy of DSME intervention in patients with T2DM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings are in line with those of the previous review that showed the positive effects of group-based self-management education interventions on HbA1c, FBG, body weight, WC, TG and diabetes knowledge [98]. Another review, however, showed that there was no effect of community-based educational interventions on SBP and DBP [99]. Overall, these findings support the potential clinical, behavioural and psychological efficacy of DSME intervention in patients with T2DM.…”
Section: Discussionsupporting
confidence: 90%
“…Second, the majority of the studies reported outcomes from less than one year follow-up, therefore the long-term effectiveness of DSME intervention in the management of T2DM population cannot be demonstrated. Third, high heterogeneity was observed in the meta-analyses for most of the outcome measures, which is likely due to variation in intervention programme design across the studies [99] as typically noted in intervention programmes of this nature. Fourth, no trial was categorised as low risk in all five components of the ROB 2 assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…The philosophy of community-based nursing is to guide nursing care for individuals, families with health problems, and other groups throughout life, wherever they are, including where they live, work and go to school, etc. According to this definition, community-based nursing is not a specialty but a philosophy that guides all nursing care [3] and have been mentioned in different studies [3,54].…”
Section: Discussionmentioning
confidence: 99%
“…Estas intervenciones proporcionaron un buen efecto sobre el control glucémico en comparación con las individuales; en particular, los programas realizados durante 12 meses en el contexto comunitario con 3 o más meses de seguimiento tuvieron mayor significancia. Según Shirvani et al 45 , las intervenciones educativas pueden reducir la incidencia de complicaciones de la DT2 por arriba de un 50%, en especial en cuanto a reducciones en la glucemia en ayunas, el IMC y la circunferencia de la cintura.…”
Section: Discussionunclassified